Residue-free peeling of EGaIn oxide enabled by contact angle control - Jung, Sangyun; Son, Jeong Gon; Dickey, Michael D.; Kim, Wonjung (Nature Publishing Group, 2025)
Gallium-based liquid metals (GBLMs) are widely used in soft machines and stretchable electronics, but their nanometer-thick surface oxide layer induces strong adhesion to substrates, making residue-free removal challenging. Conventional methods rely on harsh chemical treatments, limiting practical applications. Here, we show that the oxide layer of eutectic gallium–indium (EGaIn) can be cleanly peeled from a substrate when a sufficiently large contact angle is maintained during slow delamination. Through experimental and theoretical analysis, we show that peeling fails at small contact angles due to mechanical fracture of the oxide skin at the oxide–air interface, leaving behind residue. By examining the contact line at the nanoscale, we identify the failure mechanism governing this process. This work provides fundamental insights into the interfacial mechanics of GBLMs and establishes a framework for improving their controllability in liquid metal-based technologies.